Nolinoideae (Asparagaceae) in APG III needs replacing with Convallarioideae - Tanaka, Noriyuki; Nguyen, Khang Sinh (Phytotaxa, 2023)
Chase et al. (2009) attempted a subfamilial classification for the expanded asparagalean families Amaryllidaceae, Asparagaceae and Xanthorrhoeaceae sensu APG III (2009). In Asparagaceae they recognized seven subfamilies including Nolinoideae Burnett (1835: 985, 1095, 1106). The Nolinoideae circumscribed by them consisted of 16 genera including Nolina Michaux (1803: 207). Since the publication of their paper, the subfamily name has been adopted in many taxonomic papers (e.g. Reveal 2012, Vislobokov et al. 2018, Tanaka 2019, Averyanov et al. 2020, Nguyen et al. 2020, 2021, Meng et al. 2021).